2017
DOI: 10.1158/1078-0432.ccr-16-0083
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Precision Death with Cell-Cycle Inhibitors that Target DNA Replication and Repair

Abstract: All cancers are characterized by defects in the systems that ensure strict control of the cell cycle in normal tissues. The consequent excess tissue growth can be countered by drugs that halt cell division, and, indeed, the majority of chemotherapeutics developed during the last century work by disrupting processes essential for the cell cycle, particularly DNA synthesis, DNA replication, and chromatid segregation. In certain contexts, the efficacy of these classes of drugs can be impressive, but because they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 90 publications
1
69
0
Order By: Relevance
“…Defect in DDR related genes in tumor cells leads to impaired DNA repair, triggering apoptosis in tumor cells. Recent studies have demonstrated that DDR is important for the maintenance of tumor genome integrity, and dysregulation of DDR sensitizes tumor cells to chemotherapy [45][46][47][48]. Thus, inhibition of DDR pathway including HR and NHEJ via chemotherapeutic compounds selectively kill tumor cells that evolve to escape DDR and checkpoint signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Defect in DDR related genes in tumor cells leads to impaired DNA repair, triggering apoptosis in tumor cells. Recent studies have demonstrated that DDR is important for the maintenance of tumor genome integrity, and dysregulation of DDR sensitizes tumor cells to chemotherapy [45][46][47][48]. Thus, inhibition of DDR pathway including HR and NHEJ via chemotherapeutic compounds selectively kill tumor cells that evolve to escape DDR and checkpoint signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The phase 1 trial conducted in non‐Japanese patients observed tumor shrinkage in 10 of 34 patients, with many of these cases occurring in SCC . Squamous cell carcinoma may harbor increased levels of replication stress and/or DNA damage response, which may contribute to an increased response to CHK1/2 inhibitors . On the basis of these findings, cohorts in SCC are being evaluated in the dose‐expansion phase of the phase 1 study in non‐Japanese patients …”
Section: Discussionmentioning
confidence: 94%
“…Checkpoint kinase 1 (CHK1) is a multifunctional serine/threonine‐specific protein kinase that has a critical role in regulating response to DNA damage . The proteins ataxia telangiectasia mutated and RAD3‐related (ATR) and/or ataxia telangiectasia mutated (ATM) are activated in response to DNA damage, which in turn phosphorylate CHK1 and checkpoint kinase 2 (CHK2), respectively . p53 is another critical mediator of the response to DNA damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cell division consists of interphase and mitosis and is strictly regulated. The cell cycle checkpoint has become a therapeutic target because it is often dysregulated in cancer cells . Previous studies showed that arginine depletion could inhibit cell proliferation in human HCC and melanoma by cell cycle arrest .…”
Section: Discussionmentioning
confidence: 99%